2012
DOI: 10.1117/1.jbo.17.7.076011
|View full text |Cite
|
Sign up to set email alerts
|

Movement-related cortical activation with voluntary pinch task: simultaneous monitoring of near-infrared spectroscopy signals and movement-related cortical potentials

Abstract: Abstract. This study was designed to evaluate hemodynamic and electrophysiological motor cortex responses to voluntary finger pinching in humans, with simultaneous recording of near-infrared spectroscopy (NIRS) signals and movement-related cortical potentials (MRCP). Six healthy, right-handed subjects performed 100 trials of voluntary right-thumb index-finger pinching with about a 10-second interval at their own pace. Throughout the session, 48 regions over the bilateral motor cortex were assessed by NIRS, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
(40 reference statements)
5
7
0
Order By: Relevance
“…This reaction was consistent with the results of our previous study using simultaneous NIRS and electrocorticography recordings, although the sides of the stimulation and the recording were reversed [27]. Another of our studies also found that the hemodynamic responses to language tasks typically peak approximately 6-11 s after task stimuli [27].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This reaction was consistent with the results of our previous study using simultaneous NIRS and electrocorticography recordings, although the sides of the stimulation and the recording were reversed [27]. Another of our studies also found that the hemodynamic responses to language tasks typically peak approximately 6-11 s after task stimuli [27].…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies have supported the utility of functional NIRS analysis to assess resting state functional connectivity in the human language system [25,26]. We have also reported that simultaneous NIRS and electroencephalography recordings provide useful information about neurovascular coupling in motor [27] and epileptic networks [28]. Considering that simultaneous NIRS and transcranial magnetic stimulation provide a reliable measure of regional cortical brain activation and connectivity [29], we successfully demonstrated that NIRS recordings during direct cortical stimulation could detect cortico-cortical hemodynamic responses between the superior temporal gyrus (STG) and the inferior frontal gyrus (IFG) [30].…”
Section: Introductionmentioning
confidence: 93%
“…Additionally, our recent studies have demonstrated that simultaneous NIRS and electroencephalographic (EEG) analysis provides useful information about neural networks. 10 We also focused on ictal high-frequency oscillations (HFOs) in electrocorticography (ECoG), which are reportedly specific for detecting the SOZ and allow visualization of dynamic ictal changes.…”
Section: Introductionmentioning
confidence: 99%
“…They can also be used in combined fNIRS and EEG studies for the detection of eventrelated responses. 12,17,21 Recent studies have revealed that fNIRS signals reflect not only cerebral activity, but also systemic changes originating from both cerebral and superficial (scalp) layers. 5,[22][23][24][25][26][27] Systemic changes in the superficial (scalp) layer, which are referred to as superficial-tissue hemodynamics (scalp hemodynamics), are thought to be especially problematic because they increase in a task-related manner and may obscure movement-related cerebral activity.…”
Section: Introductionmentioning
confidence: 99%
“…Such event-related task designs are common in other types of neuroimaging, such as functional magnetic resonance imaging (fMRI) 19,20 or electroencephalography (EEG). 12,17,21 This experimental design has no constraints on the task setting and allows one to evaluate cerebral activity for single (short duration) motor events or cognitive processes (e.g., quick motor responses to an event or movement preparation), which are usually difficult to observe in a block design paradigm. In addition, event-related designs are more easily applied in a variety of real life environments and clinical scenarios when compared to block designs.…”
Section: Introductionmentioning
confidence: 99%